2019
DOI: 10.3390/ijms20133156
|View full text |Cite
|
Sign up to set email alerts
|

Real Microgravity Influences the Cytoskeleton and Focal Adhesions in Human Breast Cancer Cells

Abstract: With the increasing number of spaceflights, it is crucial to understand the changes occurring in human cells exposed to real microgravity (r-µg) conditions. We tested the effect of r-µg on MCF-7 breast cancer cells with the objective to investigate cytoskeletal alterations and early changes in the gene expression of factors belonging to the cytoskeleton, extracellular matrix, focal adhesion, and cytokines. In the Technische Experimente unter Schwerelosigkeit (TEXUS) 54 rocket mission, we had the opportunity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 76 publications
5
77
0
Order By: Relevance
“…Many studies have reported that microgravity exposure had decreased expression of actin and actin-associated proteins, namely Arp2/3 and RhoA, subsequently resulting in the disorganization of the actin cytoskeleton (Carlsson et al, 2003;Higashibata et al, 2006;Corydon et al, 2016a,b;Louis et al, 2017;Tan et al, 2018). However, other studies have showed increased F-actin and stress fiber formation that accompanied the development of lamellipodia protrusions following exposure to microgravity (Gruener et al, 1994;Nassef et al, 2019). Contrary to this, Rosner et al (2006) reported no changes to actin structure or organization and further suggested that the actin cytoskeleton is only regulated in a hyper-gravity environment.…”
Section: The Impact Of Microgravity Of Cell Cytoskeletonmentioning
confidence: 99%
“…Many studies have reported that microgravity exposure had decreased expression of actin and actin-associated proteins, namely Arp2/3 and RhoA, subsequently resulting in the disorganization of the actin cytoskeleton (Carlsson et al, 2003;Higashibata et al, 2006;Corydon et al, 2016a,b;Louis et al, 2017;Tan et al, 2018). However, other studies have showed increased F-actin and stress fiber formation that accompanied the development of lamellipodia protrusions following exposure to microgravity (Gruener et al, 1994;Nassef et al, 2019). Contrary to this, Rosner et al (2006) reported no changes to actin structure or organization and further suggested that the actin cytoskeleton is only regulated in a hyper-gravity environment.…”
Section: The Impact Of Microgravity Of Cell Cytoskeletonmentioning
confidence: 99%
“…Short-term microgravity led to an increased synthesis of ICAM-1 and VCAM-1 proteins in MDA-MB-231 breast cancer cells during a parabolic flight campaign [31]. Modulation of the expression of surface adhesion molecules such as ICAM-1 has been reported as a consequence of long-term microgravity of cultured human endothelial cells [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported that microgravity exposure changes the morphological phenotype, cell cycle, and cell adhesion, and has an impact on cell survival that is highly dependent upon the cell type, as well as on the duration of exposure [30,31]. Long-term RPM exposure of human endothelial cells induced the formation of three-dimensional tubular structures and spheroids [32].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that space flight and simulated microgravity induce significant changes in gene expression patterns, autophagy, cell migration, extracellular matrix composition and the cytoskeleton . The clinostat is widely used for space biology research, as it can simulate the effect of microgravity on cells .…”
Section: Introductionmentioning
confidence: 99%